Identifying and recruiting smokers for preoperative smoking cessation—a systematic review of methods reported in published studies. Issue 1 (December 2015) - Song, Fujian; Brown, Tracey; Blyth, Annie; Maskrey, Vivienne; McNamara, Iain; Donell, Simon
Abstract Background Smoking cessation before surgery reduces postoperative complications, and the benefit is positively associated with the duration of being abstinent before a surgical procedure. A key issue in providing preoperative smoking cessation support is to identify people who smoke as early as possible before elective surgery. This review aims to summarise methods used to identify and recruit smokers awaiting elective surgery. Methods We searched MEDLINE, EMBASE, CINAHL, and PsycINFO, and references of relevant reviews (up to May 2014) to identify prospective studies that evaluated preoperative smoking cessation programmes. One reviewer extracted and a second reviewer checked data from the included studies. Data extracted from included studies were presented in tables and narratively described. Results We included 32 relevant studies, including 18 randomised controlled trials (RCTs) and 14 non-randomised studies (NRS). Smokers were recruited at preoperative clinics (n = 18), from surgery waiting lists (n = 6), or by general practitioners (n = 1), and the recruitment methods were not explicitly described in seven studies. Time points of preoperative recruitment of smokers was unclear in four studies, less than 4 weeks before surgery in 17 studies, and at least 4 weeks before surgery in only 11 studies. The recruitment rate tended to be lower in RCTs (median 58.2 %, range 9.1 to 90.9 %) than that in NRS (median 99.1 %, range 12.3 to 100 %) and lower in preoperative clinic-based RCTs (median 54.4 %, range 9.1 to 82.4 %) than that in waiting list-based RCTs (median 70.1 %, range 36.8 to 85.0 %). Smokers were recruited at least 4 weeks before surgery in four of the six waiting list-based studies and in only three of the 18 preoperative clinic-based studies. Conclusions Published studies often inadequately described the methods for recruiting smokers into preoperative smoking cessation programmes. Although smoking cessation at any time is beneficial, many programmes recruited smokers at times very close to scheduled surgery so that the benefit of preoperative smoking cessation may have not been fully effected. Optimal delivery of preoperative smoking cessation remains challenging, and further research is required to develop effective preoperative cessation programmes for smokers awaiting elective operations.